Students’ Mathematical Literacy Ability from van Hiele’s Theory in Geometry - Azmi, Septiana Ulul; Sukestiyarno, Sukestiyarno; Rochmad, Rochmad (Jurnal Pendidikan MIPA, 2023)
Mathematical literacy in Indonesia in 2015 saw the results of the Pisa show that it was ranked 62 out of 70 countries by obtaining a score of 386. That the mathematical literacy of Indonesian students is not satisfactory or can be said to be low. The method used in this research is qualitative research. The purpose of this study was to describe students' mathematical abilities in terms of Van Hiele's theory. Data collection techniques include (1) test questions, (2) interviews, and (3) documentation. Data supporting data analysis used includes data reduction, data presentation, and drawing conclusions. The results obtained were that students with level 3 at Van Hiele were included in the high level category at the junior high school level able to complete 6 indicators of mathematical literacy well, which means students with level 3 Van Hiele then mathematical literacy would be high. Students with level 1 on moderate Van Hiele are only able to complete 4 indicators of mathematical literacy well because students are only able to design strategies but are still lacking in using mathematical tools, while students with level 0 on low Van Hiele are only able to complete 2 indicators of mathematical literacy well because students are less able to design strategies because in the process students are still hesitant in solving a problem. Keywords: mathematical literacy, van Hiele theory, junior high school students.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp124-134